КУРАШДА СПОРТ ТРАВМАТИЗМИ ТАҲЛИЛИ ВА УНИ КАМАЙТИРИШГА ОИД ТАДБИРЛАР ИШЛАБ ЧИҚИШ - Еримбетов, Б.Қ. (SCIENCE and SOCIETY, 2023)
This article is analyzed the need to train qualified specialists in the development of physical education and wrestling sports in our country, as well as the athlete’s training period, athlete’s age, qualification, morphological, anthropometric, anatomical-functional characteristics.